Outcomes of aortic valve repair: early results from the German Aortic Valve Registry. (13th August 2022) - Girdauskas, Evaldas; Petersen, Johannes; Balaban, Ümniye; Herrmann, Eva; Bauer, Timm; Beckmann, Andreas; Bekeredjian, Raffi; Ensminger, Stephan; Frerker, Christian; Möllmann, Helge; Walther, Thomas; Bleiziffer, Sabine
Abstract: OBJECTIVES: Aortic valve (AV) repair is an evolving surgical strategy in the treatment of young patients with aortic regurgitation (AR) and/or aortic root aneurysm. We aimed to determine the clinical outcome following AV repair/AV-sparing root surgery using real-world data from the German Aortic Valve Registry. METHODS: A total of 2327 patients with AR (mean age 55.2 ± 15.0 years, 76% men), who underwent AV repair/AV-sparing root surgery between 2011 and 2015 (i.e. 5% of 42 868 AV surgery patients enrolled in the German Aortic Valve Registry during the same period) were included. Study cohort was subdivided according to the technique of AV repair: isolated AV repair without root surgery (group I) ( n  = 914), AV-sparing root surgery (i.e. reimplantation or remodelling) without cusp repair (group II) ( n  = 1077) and AV-sparing root surgery (i.e. reimplantation or remodelling) with simultaneous cusp repair (group III) ( n  = 336). Primary end point was 1-year survival after AV repair/AV-sparing root surgery. Secondary end points were freedom from cardiac adverse events and freedom from AV reinterventions at 1-year follow-up. RESULTS: Thirty-day mortality was 19 (0.8%) in the whole study cohort without significant differences in the 3 subgroups [4 (0.4%) patients in group I vs 14 (1.3%) patients in group II vs 1 (0.3%) patient in group III ( P  = 0.054)]. Postoperatively, 1445 (74%) patients had no residual AR, 474 (24%) patients had mild AR and 40 (2%) patients had moderate/severe AR at the time of hospital discharge. One-year survival (95% confidence interval) was 97.7% (97.1–98.3) in the whole study cohort and without significant difference among the 3 subgroups. One-year cardiac adverse event-free survival (95% confidence interval) was 85.7% (84.2–87.1) and was similar in all 3 study groups in propensity score-weighted analysis. A total of 38 (1.6%) patients required AV reintervention during a 1-year follow-up, without significant difference among subgroups ( P  = 0.11). CONCLUSIONS: AV repair/AV-sparing root surgery is performed in 5% of patients requiring AV surgery in Germany. Our data demonstrate very satisfactory periprocedural and 1-year survival and cardiac event-free survival after AV repair surgery. Implementation of specific surgical techniques during the index procedure seems to result in comparable outcomes. Abstract : Aortic regurgitation (AR) is a multifactorial disease with a reported prevalence between 1% and 13% in the population-based studies [1, 2].